Business Feasibility Analysis of Refill Drinking Water Enterprises:: A Case Study of the Moses Agent in Batang Regency - Cahyaningsih Cahyaningsih; M. Taufiq Abadi (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study aims to analyze the business feasibility of a refill drinking water enterprise, taking theMoses Agent in Batang Regency as a case study. The research examines the enterprise’s viabilityfrom legal, market, technical, and financial perspectives to determine its potential forsustainable operation and profitability. A quantitative descriptive approach was applied,supported by data collection through observation, interviews, and documentation. Financialfeasibility was assessed using several indicators, including Net Present Value (NPV), Internal Rateof Return (IRR), Payback Period (PP), and Profitability Index (PI). The resultsshow that the MosesAgent business meets all feasibility criteria, with an NPV value of IDR 48,004,741, an IRR of 23.22percent, a Payback Period of 3.75 years, and a PI greater than one, indicating a financially viableinvestment. From the non-financial aspect, the business also fulfills the legal, human resource,and market requirements for operation. These findings suggest that refill drinking waterenterprises have strong potential to support local economic development and meet communitydemand for affordable, hygienic drinking water. This study contributes to the broaderunderstanding of small-scale business sustainability and provides practical implications forentrepreneurs and local governments in developing similar enterprises within Indonesia’smicroand small enterprise sector.